Magainin 2 and PGLa in Bacterial Membrane Mimics II: Membrane Fusion and Sponge Phase Formation - Kabelka, Ivo; Pachler, Michael; Prévost, Sylvain; Letofsky-Papst, Ilse; Lohner, Karl; Pabst, Georg; Vácha, Robert (Biophysical journal, 2020)
We studied the synergistic mechanism of equimolar mixtures of magainin 2 (MG2a) and PGLa in phosphatidylethanolamine/phosphatidylglycerol mimics of Gram-negative cytoplasmic membranes. In a preceding article of this series, we reported on the early onset of parallel heterodimer formation of the two antimicrobial peptides already at low concentrations and the resulting defect formation in the membranes. Here, we focus on the structures of the peptide-lipid aggregates occurring in the synergistic regime at elevated peptide concentrations. Using a combination of calorimetric, scattering, electron microscopic, and in silico techniques, we demonstrate that the two peptides, even if applied individually, transform originally large unilamellar vesicles into multilamellar vesicles with a collapsed interbilayer spacing resulting from peptide-induced adhesion. Interestingly, the adhesion does not lead to a peptide-induced lipid separation of charged and charge-neutral species. In addition to this behavior, equimolar mixtures of MG2a and PGLa formed surface-aligned fibril-like structures, which induced adhesion zones between the membranes and the formation of transient fusion stalks in molecular dynamics simulations and a coexisting sponge phase observed by small-angle x-ray scattering. The previously reported increased leakage of lipid vesicles of identical composition in the presence of MG2a/PGLa mixtures is therefore related to a peptide-induced cross-linking of bilayers.
Keywords: magaininy; Phosphatidylglycerols; Magainins; fosfatidylglyceroly; Membrane Fusion; buněčná membrána; Cell Membrane; Lipid Bilayers; lipidové dvojvrstvy; fúze membrán